Pengaruh Pola Makan Sehat terhadap Kesehatan Jantung pada Lansia - Arbi Kusuma; Zubiyan Munandar (Journal of Applied Health Sciences, 2025)
Heart health is a crucial aspect of maintaining the quality of life in the elderly, as the risk of cardiovascular disease increases with age. A healthy diet consisting of balanced nutrition, low saturated fat, low sodium, and high fiber has been proven to play a significant role in maintaining cardiovascular function. This study aims to analyze the effect of a healthy diet on heart health in elderly individuals. A quantitative approach with a cross-sectional design was applied to 120 respondents aged ≥ 60 years at Puskesmas X. Data were collected through a dietary pattern questionnaire and heart health assessments, including blood pressure, cholesterol levels, and body mass index. Data analysis was conducted using multiple linear regression tests to examine the relationship and effect of diet on heart health variables. The results showed that a healthy diet had a significant positive effect on heart health in the elderly (p < 0.05), where elderly individuals who regularly consumed fruits, vegetables, fish, and whole grains tended to have normal blood pressure and lower cholesterol levels. These findings emphasize the importance of adopting a healthy diet as a preventive strategy against heart disease in older adults. The study recommends continuous nutrition education and dietary guidance programs to improve heart health among the elderly.